Development as a Battlefield - Bono Béatrice Hibou, Irene (International Development Policy, 2017)
Development as a Battlefield is an innovative exploration of conflict and development, phenomena that are often regarded as ostensibly antagonistic. It invites readers to reconsider socio-political and economic developments in the MENA region and beyond. Readership: Academic libraries and institutional libraries, scholars and post-graduate students, development and policy specialists and practitioners interested in the development-conflict nexus, global security, international relations, development cycles, development policy and practice, citizens' role in society, anthropology, history, political sociology and political economy, globalisation, migration, women, the Middle East and North Africa.